ii ii PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP ROA PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2024 - Calista Raysa Sabita; Neng Dalia Ramadani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of Loan to Deposit Ratio (LDR), Operating Expenses to Operating Income (BOPO), Non-Performing Loan (NPL), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), and Gross Domestic Product (GDP) on profitability as measured by Return on Assets (ROA) in conventional commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. This research employs a quantitative approach using panel data regression analysis. Based on the Chow and Hausman tests, the Random Effect Model is selected as the most appropriate model. The sampling technique used is purposive sampling based on specific criteria. The results indicate that BOPO, CAR, and NIM have a significant effect on ROA, while LDR, NPL, and GDP do not have a significant effect on ROA. These findings suggest that bank profitability is more influenced by internal factors, particularly operational efficiency, rather than macroeconomic conditions.